2001
DOI: 10.1115/1.3097287
|View full text |Cite
|
Sign up to set email alerts
|

Multiparticle Effective Field and Related Methods in Micromechanics of Composite Materials

Abstract: The numerous approaches used in micromechanics can be classified into four broad categories: perturbation methods, self-consistent methods of truncation of a hierarchy, variational methods, and the model methods. In detail we will consider the self-consistent methods applied to linear elastic problems, based on some approximate and closing assumptions for truncating of an infinite system of integral equations involved and their approximate solution. We consider multiparticle effective field methods, effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 0 publications
0
98
0
Order By: Relevance
“…The second moment of the strain field is obtained by derivation of the effective energy of the composite with respect to the elastic moduli L (r) of the individual phases (see for instance Ponte Castañeda and Suquet, 1998, Buryachenko, 2001or Ponte Castañeda, 2002 :…”
mentioning
confidence: 99%
“…The second moment of the strain field is obtained by derivation of the effective energy of the composite with respect to the elastic moduli L (r) of the individual phases (see for instance Ponte Castañeda and Suquet, 1998, Buryachenko, 2001or Ponte Castañeda, 2002 :…”
mentioning
confidence: 99%
“…Following the argumentation in [48,49], the elastic predictor can be obtained in each phase from the second statistical moment estimation of the total strain, as…”
Section: Elastic Predictormentioning
confidence: 99%
“…Estimation of effective elastic moduli of nanocomposites was performed by the means of effective field method (MEF, see for references and details [1]) based on a so-called effective field hypothesis: each fiber is embedded in the homogeneous effective field depending on prescribed random orientation of this fiber [in contrary to the Mori-Tanaka method (MTM) where the effective field coincides with the average stresses in the matrix]. It may be noted the certain drawbacks of the extension of MoriTanaka method to multiphase composites: Mori-Tanaka moduli may violate the Hashin-Shtrikman bounds and are non-symmetric for the general diphase composites.…”
Section: Estimation Of Effective Moduli Of Nanocompositesmentioning
confidence: 99%
“…For example, many studies have shown that both tensile ductility and fracture properties of multi-phase composite materials are strongly affected by the spatial heterogeneity of the reinforcing phases (see for references e.g. [1]). Even after many years of comprehensive study by extremely laborious direct measurements and empirical relations, the effect of the structure of microinhomogeneous materials and their influence on the mechanical properties is not completely clear.…”
Section: Introductionmentioning
confidence: 99%